PHONEME CHANGES IN ENGLISH LOANWORDS FROM ARABIC (A STUDY OF PHONEME CHANGE PATTERNS IN GRIMM'S LANGUAGE MODEL) - Musthofa Musthofa; Vika Wafa Ilmi; Sahiron Sahiron (Sunan Kalijaga State Islamic University Yogyakarta, 2026)
This article is part of a historical linguistic study on word nativization caused by cultural contact between two nations with different languages. Cultural contact causes language contact, language contact causes word adoption from other languages, which then leads to phonemic changes. What are the phonemic changes in English loanwords from Arabic? What is the pattern? The researchers discuss phonemic changes in English loanwords of Arabic, based on the analogy of Grimm's Law regarding phonemic change patterns. It aims to identify English loanwords derived from Arabic and the patterns of phonemic change. The method used in this study is comparative descriptive. The results of this analysis include the discovery of 50 phoneme change patterns in English loanwords from Arabic. The 50 patterns were then further classified to obtain 22 groups of phoneme change patterns. In terms of the form of change, these 22 change patterns can be classified into five forms of phoneme change. 1) Phoneme replacement, 2) Phoneme deletion/elimination, 3) Phoneme addition, 4) Phoneme shift, and 5) Drastic and extreme changes in loanwords that are almost impossible to recognize as loanwords.